The energyscape of the lower Thames and Medway: Britain's changing patterns of energy use. (2nd January 2020) - Murray, Stephen
ABSTRACT: This article examines the history of the energy landscape — the energyscape — of the lower River Thames and Medway from the 1860s to the present. It explores why, and in what ways, the energy industries have exploited the area and its landscape. Key factors include its accessibility for ocean-going shipping; the proximity to energy consumers in London and south-east England; the availability of large areas of land; and water resources. The energy industries included oil storage and refining; petrochemicals; gas manufacture and handling; and electricity generation and distribution. The article argues that the development of energy infrastructure in the Thames/ Medway landscape reflects the shifting patterns of energy use in the UK. For example, the recent demolition of Grain and Kingsnorth power stations — prominent north Kent landmarks since the 1970s — exemplifies the decline of coal and oil as primary fuels for electricity generation. Similarly, the seascape of the outer Thames estuary has been transformed by the advent of renewable energy and the construction of four major offshore wind farms. The article demonstrates how patterns of energy use are a mosaic of social needs, technological capabilities, environmental concerns, political expediency, and economic forces. The Thames/ Medway energyscape has developed, evolved and been adapted to these influences, and continues to support the energy needs of the UK economy.